Chaotic dynamics of flexible beams driven by external white noise; Mechanical Systems and Signal Processing; Vol. 79 : Special Issue from ICEDyn 2015 - Awrejcewicz J.; Krysko A. V. Anton Vadimovich; Papkova I. V.; Zakharov V. M.; Erofeev N. P.; Krylova E. Yu.; Mrozowski J.; Krysko V. A. (2016, 2016)
Title screen